2013
DOI: 10.17795/acr-12476
|View full text |Cite
|
Sign up to set email alerts
|

Cytotoxic/Proliferative Effects of Umbelliprenin on Colon Cancer Cell Lines

Abstract: Background: Colon carcinoma growth depends on many factors such as, different organisms, and immune cells, which induce and produce inflammatory cytokines. Umbelliprenin is a naturally prenylated coumarin with anti-inflammatory activities. Its ability to induce cancer cell death has shown variation on different cancer cell lines. Objectives: 7-Prenyloxycoumarins, including umbelliprenin have been widely investigated because of their pharmacological activities. This paper shows the effect of umbelliprenin on co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…In addition, multiple regulatory proteins can be affected upon treatment with UMB. A study suggested down-regulation of many important proteins, i.e., tubulin α-1B, HSP90, HSP27, hnRNP C1/C2, Cyclophilin, and tumor suppressor MST protein, and up-regulation of stathmin and calreticulin in lung cancer cell lines, i.e., QU-DB and A549 [70].…”
Section: Lung Cancermentioning
confidence: 99%
“…In addition, multiple regulatory proteins can be affected upon treatment with UMB. A study suggested down-regulation of many important proteins, i.e., tubulin α-1B, HSP90, HSP27, hnRNP C1/C2, Cyclophilin, and tumor suppressor MST protein, and up-regulation of stathmin and calreticulin in lung cancer cell lines, i.e., QU-DB and A549 [70].…”
Section: Lung Cancermentioning
confidence: 99%
“…1 H NMR spectra were recorded on a Bruker Advance 500 III HD spectrometer at a nominal frequency of 500.11 MHz. 13 C NMR spectra were recorded on a NMR Bruker DRX 400 spectrometer. A Waters CGT Premier mass spectrometer with a chemical ionization source (CI) with methane reagent gas was used for mass spectrometry analysis of degradation products.…”
Section: ■ Experimental Sectionmentioning
confidence: 99%
“…This oxyprenylated coumarin is commonly found in different plant species such as Ferula , Peucedanum , Seseli , Magydaris , and Ammi , but also in some edible fruits and vegetables such as celery ( Apium graveolens L.), wild celery ( Angelica archangelica L.), and Citrus lemon . , Umbelliprenin was shown to exert anti-inflammatory, immunomodulatory, and anticancer activities . A mechanism of action underlying these effects includes inhibition of matrix metalloproteinases and pro-inflammatory enzymes (e.g., lipoxygenase), antioxidant and antigenotoxic properties, chemoprevention of tumors such as papilloma, colorectal, melanoma, and breast carcinomas, induction of apoptosis, abolition of P-glycoprotein-mediated multidrug-resistance, and up-regulation of Mcl-1. The importance of the in vitro overall stability of drug candidates is nowadays well recognized. In this context a limited number of studies on coumarins have been reported. The first report dates back to 1957 and has been based merely on the isolation and structure characterization (elemental analysis and mixed melting point) of these compounds .…”
mentioning
confidence: 99%
“…The two different actions may be attributed to the fact that umbelliprenin possesses different apoptotic actions in different cell lines (Barthomeuf, Lim, Iranshahi, & Chollet, 2008). This study emphasised that umbelliprenin can be a future cytotoxic compound but with a simultaneous emphasis on personalised medicinal approach (Hamidinia, Ramezani, & Mojtahedi, 2013). 6,7-dihydroxycoumarin (Esculetin) has also been found to decrease the viability and growth of various human colon cancer cell lines.…”
Section: Citrus Limonoids Mechanism Of Anticancer Activity Referencesmentioning
confidence: 99%